The Role Of Promotional Mix Elements In The Behavior Of Mobile Phone Recipients A Field Study On Customers Of Syriatel Cellular Communications Company In Lattakia City (مجلة جامعة اللاذقية- سلسلة العلوم الاقتصادية والقانونية, 2020)
This study aimed to identify the role of the promotional mix elements in the behavior of the recipients of cellular phone services dealing with Syriatel cellular communications company in Lattakia city. The researcher adopted the deductive approach as a general approach to research, The researcher distributed the questionnaire to (312) individual, and the researcher adopted in the analysis on the program SPSS 20, The results concluded that there was a significant correlation between the promotional mix elements of the company in question and the behavior of the recipients of the cellular phone customers. That is, there is an impact of the promotional mix elements (advertising, personal selling, sales promotion, public relations) on the behavior of the recipients of cellular services of the company under study, The study then made some recommendations, the most important of which were: The importance of the management of the company to the promotional mix strategies more as a factor influencing the work of the company in general, and in influencing the behavior of consumers in particular, through the following: The need to allocate significant resources to the promotional mix, and to try to coordinate between its elements in order to make it more effective by influencing the behavior of consumers, as well as the precise identification of factors influencing the behavior of the target consumer, and study them well, and then develop the appropriate promotional strategy to gain satisfaction, and achieve loyalty.هدفت هذه الدراسة إلى التعرُّف على دور عناصر المزيج التّرويجي في سلوك مُتلقيّ خدمات الهواتف الخلوية المُتعاملين مع شركة سيرياتيل للاتِّصالات الخلوية في مدينة اللاذقية, واعتمد الباحث على منهج المقاربة الاستنباطية كمنهج عام للبحث, وقام الباحث بتوزيع الاستبيان على (312) مفردة, واعتمد الباحث في تحليلها على برنامج SPSS 20, وخلصت النّتائج إلى وجود علاقة ذات دلالة معنوية بين عناصر المزيج التّرويجي للشركة محلّ الدراسة, وبين سلوك مُتلقيّ خدمات الهواتف الخلوية المُتعاملين معها؛ أيّ أنَّ هناك تأثير لعناصر المزيج التّرويجي والمتمثِّلة في (الإعلان, والبيع الشخصي, وتنشيط المبيعات, والعلاقات العامَّة) على سلوك مُتلقيّ خدمات الهواتف الخلوية للشركة محلّ الدراسة, ثم قدَّم الباحث بعض التوصيّات والتي كان من أهمّها: ضرورة اهتمام إدارة الشركة باستراتيجيات المزيج التّرويجي بشكل أكبر باعتبارها عاملاً مؤثراً في عمل الشركة بشكلٍ عام, وفي التأثير في سلوك المُستهلكين بشكلٍ خاص وذلك من خلال الآتي: ضرورة تخصيص موارد هامة للمزيج التّرويجي, ومحاولة التنسيق بين عناصره بما يجعله أكثر فاعلية بالتأثير على سلوك المُستهلكين, وكذلك التحديد الدقيق للعوامل المؤثِّرة في سلوك المُستهلك المُستهدف, ودراستها جيداً, ثم وضع الإستراتيجية التّرويجية المناسبة لكسب رضاه, وتحقيق ولاءه.